Study on Influencing Factors of Liquid Carbon Dioxide Blasting in Rock Cutting - Li, Jianwei; Zhang, Guiwen; Liu, Huadong; Zhang, Shanglong; Cheng, Xuansheng (Recent Patents on Engineering, 2024)
Background: At present, although some scholars have studied liquid carbon dioxide blasting, there are still some problems to be solved, such as the influencing factors of the liquid carbon dioxide blasting effect. Based on the project of Jiu’e railway, this paper studies the influencing factors of liquid carbon dioxide blasting in rock cutting. Objective: The patent study aims to show the influence of different blasting hole depths and jet directions on the effect of liquid carbon dioxide blasting and fracture development. Methods: Considering the influence of jet direction and different blasting hole depth on liquid carbon dioxide blasting in rock cutting, the fracture development law at different blasting hole depths is analyzed, the stress characteristics of jet direction and non-jet direction are discussed, and fracture development process is analyzed in detail from the viewpoint of energy. Moreover, related patents on liquid carbon dioxide blasting devices are also reviewed. The research on law of fracture development and optimal blasting hole depth is the highlight of this paper. Results: The influence of different blasting hole depths, jet directions on effect of liquid carbon dioxide blasting and fracture development is analyzed, When the depth of blasting hole is 2.5 m, the fractures can extend to bench surface but cannot extend to the bottom of the excavation surface. When the hole depth is 5.0 m, the fractures cannot extend to the bench surface. The fractures can be extended to the bottom of the excavation face and the bench surface when the blasting hole depth is 4.0. Moreover, the liquid carbon dioxide blasting can effectively blast the rock cutting, and the optimal blasting hole depth is 4 m. Conclusion: Through the analysis results, considering the influencing factors of fracture number, fracture length and consumption of blasting energy, a blasting hole depth of 4 m is considered the best option.
Keywords: jet effect